Literature Review: Kepuasan Perawat Dalam Pendokumentasian Asuhan Keperawatan Meggunakan Sistem Informasi Di Rumah Sakit - Eva Riyani; Rr Tutik Sri Hariyati (Jurnal Keperawatan Muhammadiyah, 2022)
Introduction: The use of information system technology in hospitals has been implemented and is growing rapidly in the world and in Indonesia. Nursing as part of services in hospitals also plays a role in providing knowledge, nursing data, patient information needed by documenting nursing care. Objective: To evaluate nurses’ satisfaction is one method to ensure the usefulness of an information system. Methods: This study uses a literature review method that is searched through electronic databases, namely ProQuest, Science Direct, and Google Scholar with the inclusion criteria of articles that have titles and content relevant to the research objectives, using English and Indonesian full text, and articles published in 2016-2020. Results: There were ten research articles that matched the inclusion criteria with the results that most of the nurses were satisfied with the use of information systems in the documentation of nursing care. Conclusion: Nurse satisfaction in using an electronic documentation system can help the management of a hospital for the development of information systems in the context of nursing care, making decisions and policies related to investment in information systems.Keywords: electronic documentation; nurses’ satisfaction; information system